Severe dengue with fulminant myocarditis and acute coronary syndrome in a young woman:case report. - Belmontes-Gutiérrez , D.A; Isais-Moreno , D.M.; Castro-Ruales , J.M.; Hernández-Aguirre , U.G.; Moreno Velasco , P.A. (Revista de Ciencias Médicas Torreón, 2026)
Dengue is an endemic viral disease that is usually self-limited but may progress to severe organ dysfunction. Cardiovascular involvement is uncommon and can present as myocarditis, arrhythmias, or a clinical picture mimicking acute coronary syndrome. We report a 34-year-old woman with hypertension and class II obesity with confirmed dengue who developed intense abdominal pain, metabolic acidosis, elevated troponin I and CK-MB, and ST-segment elevation in leads V2–V4. Point-of-care echocardiography showed apical hypokinesia and systemic venous congestion, raising the differential diagnosis of fulminant myocarditis versus acute myocardial infarction. Given the high bleeding risk inherent to severe dengue, initial antiplatelet therapy was withheld. Despite early transfer to a tertiary center, the patient deteriorated rapidly, developing cardiogenic shock and cardiac arrest with fatal outcome. This case highlights the diagnostic and therapeutic challenges of dengue-related myocardial injury and underscores the need for early recognition and individualized management.